Remediation of lead toxicity by exogenous application of silicon in rice: Remediation of lead toxicity in rice - Pranto, S; Haque, M A; Islam, S; Dhrubo, P S; Soha, M M; Lamia, F N; Rahman, M L (Bangladesh Journal of Agriculture, 2025)
Silicon (Si) application is reported to be very effective in mitigating different stresses; however, their impact on mitigating heavy metals, especially lead (Pb) toxicity has not been previously investigated. The objective of the current experiment was to assess the consequences of different silicon sources and rates on plant parameters of rice under Pb toxic soil condition. The study was set up at the net house of the Department of Soil Science of Patuakhali Science and Technology University during the monsoon 2024. A two factors completely randomized design with three replications was assigned to the study. Two levels of lead (0 and 100 mg Pb kg-1 soil as lead nitrate), and two sources of silicon (Ca silicate and Fumed silica), both at 50 and 100 mg Si kg-1 soil, were applied on BINA Dhan-23. The results revealed that Pb stress significantly (p < 0.05) reduced the shoot dry weight of rice (11.0 and 10.4 g pot-1 in Pb control and 100 mg Pb kg-1 soil treatment, respectively), whereas Si application improved the shoot dry weight. There was a strong antagonistic relation of Si with uptake of Pb by the plants. Increasing Si rates, the Pb content in shoot and root gradually decreased, with the lowest Pb contents recorded at 100 mg Si kg-1 soil treatment. Among the two Si sources, the fumed silica had a higher capacity to reduce Pb content by both shoot and root than calcium silicate. The Pb accumulation in the root was several folds higher than shoot. Although, 100 mg Si kg-1 soil was found promising to reduce Pb toxicity in plants; more dose of Si is needed to apply in future research to find out the effects of most dose of Si on the extent of reduction of Pb toxicity in plants. Bangladesh J. Agri. 2025, 50(1): 1-19